Influence of Late Victorian English Dramaturgy on the Formation of B. Shaw Aesthetics (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This paper investigates the influence of late Victorian English dramaturgy on Bernard Shaw’s aesthetics, focusing on how the era’s realism, social critique, and moral didacticism shaped his works. Shaw adopted and redefined these elements, transforming drama into a platform for intellectual debate and societal reform. Through an analysis of plays like Mrs. Warren’s Profession and Pygmalion, the study highlights Shaw’s innovative fusion of Victorian traditions with modernist ideals, establishing his legacy as a transformative force in modern theater.